Comparative study of laparoscopic and open surgery in management of 50 cases of liver hydatid cyst - Gohil, Vikram B.; Thakur, Swarnim U.; Mehta, Smit M.; Dekhaiya, Firdaus A. (International Surgery Journal, 2020)
Background: Echinococcosis is caused by parasite called Echinococcus granulosus and Echinococcus multilocularis. The modern treatment of hydatid cyst of the liver varies from surgical intervention to percutaneous drainage or medical therapy. Methods: This clinical study was done on 50 patients who had liver hydatid disease admitted in Sir T Hospital, Bhavnagar from August 2013 to February 2016. Patients were divided into two groups consisting of 25 cases in each. Group A: managed by open surgery. Group B: managed by laparoscopic surgery. All patients followed up for 6 months after surgery. Results: The mean operative time in Group A was 65.2 minutes (range 35-100 minutes) while in Group B it was 76.32 minutes (range 50-100 minutes). Group B patients were mobilised early and resumed duty very fast then Group A. The mean duration of stay in hospital was 12.4 days (range 4-20 days) in Group A and 6.2 days (range 4-12 days) in Group B. Wound infection seen in 16% in Group A and 0% in Group B. General complication rate was 32% in Group A and 8% in Group B. No recurrence noticed in either group during follow up. Conclusions: Overall laparoscopic management of liver hydatid cyst is cost effective in terms of early mobilization, early discharge and early resumption of work along with cosmetic benefit.